Dietary olive‑garlic extract oil supplementation: influence on performance and haematological indices of broilers - Williams Gabriel Adedotun; Babatunde Adetutu Victoria; Bello Fatimah Damilola; Alausa Bolajoko Suliat; Adewale Adebayo Oluwafemi (Agricultura Tropica et Subtropica)
The use of antibiotic growth promoters in broiler production has been the norm in developing countries, however, the increased rate of antibiotic resistance in humans has resulted in the search for alternatives without negative residual effects. This study investigated the effect of dietary olive garlic extract oil (OGEO) supplementation on the performance and haematological indices of broilers. The experiment lasted for 42 days and broilers were fed varying levels of OGEO‑supplemented diets at the starter (0–21 days) and finisher (22–42 days) phases using two hundred and forty unsexed Ross broilers. Four experimental diets were formulated for the two phases and the diets were designated as diet 1(control (without OGEO)) while diets 2, 3, and 4 were supplemented with OGEO at 1 % (10 g/kg diet) 3 % (30 g/kg diet) and 5 % (50 g/kg diet). Each had four replicates containing fifteen birds per replicate. Performance was measured weekly and haematological indices were determined on days 21 and 42. Data collected were analysed in a one‑way analysis of variance (SAS, 2000) and significant differences were determined using Tukey’s test. Body weight (BW) increased linearly (L) (p = 0.003) and quadratically (Q) (p = 0.006) with dietary supplementation of OGEO at 1 % for broilers on day 21. Similarly, at day 42, BW increased (L, p = 0.006; Q, p = 0.029) for the broiler on the same treatment. Mortality reduced (Q, p = 0.035) for broilers fed 1 % OGEO‑supplemented diet at day 42. At day 21, Packed cell volume (PCV, 47.33 %) (Q, p = 0.033) and mean corpuscular volume (MCV, 130.83pg) (Q, p = 0.008) increased for broilers fed 1 % and 3 % OGEO supplemented diet respectively. Supplementation of OGEO at 3 % increased (Q, p = 0.036) PCV (37.33 %) and haemoglobin (Q, p = 0.021) (137.30 g/L) at day 42. In conclusion, the supplementation of OGEO in the diet of broilers at 1 % resulted in improved WG and reduced mortality. The PCV and haemoglobin of broilers can be increased with the supplementation of OGEO up to 3 % in the diet of broilers; it is thus a suitable alternative to antibiotics for improved performance and immunity.